2021
DOI: 10.1080/09546634.2021.1914308
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in sleep and itch and enhanced quality of life in adult patients with moderate-to-severe atopic dermatitis: results from a phase 3 trial of baricitinib therapy

Abstract: Background: Baricitinib previously demonstrated improvements in itch and sleep disturbance versus placebo in adults with moderate-to-severe atopic dermatitis (AD). Objectives: Examine if itch and sleep improvements are associated with better quality of life (QoL) and productivity in patients with AD. Methods: Data were drawn from BREEZE-AD5 (NCT03435081). Itch and sleep improvement at Week 16 were defined using !4-point improvements in the Itch Numeric Rating Scale and !1.5 decreases in the number of nighttime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Data in support of the impact of baricitinib treatment on DLQI and work productivity were reported for the originating study BREEZE‐AD5 9 . More recently, it was demonstrated that improvements in itch and sleep with baricitinib translate into meaningful improvements in patients' daily lives 23 . Taken together, these findings indicate that alleviation of these core symptoms of AD with baricitinib contribute toward important improvements in overall disease burden for patients.…”
Section: Discussionmentioning
confidence: 72%
“…Data in support of the impact of baricitinib treatment on DLQI and work productivity were reported for the originating study BREEZE‐AD5 9 . More recently, it was demonstrated that improvements in itch and sleep with baricitinib translate into meaningful improvements in patients' daily lives 23 . Taken together, these findings indicate that alleviation of these core symptoms of AD with baricitinib contribute toward important improvements in overall disease burden for patients.…”
Section: Discussionmentioning
confidence: 72%
“…For patients with a baseline Atopic Dermatitis Sleep Scale score ≥1.5, a decrease of at least 1.5 points in the number of nighttime awakenings caused by itch was observed for both 1 mg ( P =.04) and 2 mg ( P <.001) versus placebo. Adverse effects were not mentioned [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary end point was the percentage of patients with a vIGA-AD of 0-1 at week 32, 52, and 68 of continuous therapy, and both dosages of baricitinib provided long-term efficacy [35]. Baricitinib plus TCSs has also proven its efficacy in controlling disease-related sleep and itch and positively impacted the QoL of patients with moderate-to-severe AD [36][37][38].…”
Section: Baricitinibmentioning
confidence: 99%